2016
DOI: 10.1371/journal.pone.0153327
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characterization of the Effects of Cannabis Smoke and Anandamide in Rats

Abstract: Cannabis is the most widely used illicit drug in the world. Delta-9-tetrahydrocannabinol (Δ9-THC) is the main psychoactive component of cannabis and its effects have been well-studied. However, cannabis contains many other cannabinoids that affect brain function. Therefore, these studies investigated the effect of cannabis smoke exposure on locomotor activity, rearing, anxiety-like behavior, and the development of dependence in rats. It was also investigated if cannabis smoke exposure leads to tolerance to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 75 publications
3
52
1
Order By: Relevance
“…Similar effects have also been demonstrated following inhalation of THC (or cannabis smoke) but efficacy may be more variable. SR blocked hypolocomotive effects of marijuana smoke inhalation in rats (Bruijnzeel et al, 2016) and fully blocked antinociception caused by aerosolized THC, but only partially blocked the antinociceptive effects of cannabis smoke inhalation, in male ICR mice (Lichtman et al, 2000;Lichtman, Poklis, Poklis, Wilson & Martin, 2001). Catalepsy caused by marijuana smoke inhlation was not blocked by SR pretreatment in the latter study.…”
Section: Introductionmentioning
confidence: 55%
“…Similar effects have also been demonstrated following inhalation of THC (or cannabis smoke) but efficacy may be more variable. SR blocked hypolocomotive effects of marijuana smoke inhalation in rats (Bruijnzeel et al, 2016) and fully blocked antinociception caused by aerosolized THC, but only partially blocked the antinociceptive effects of cannabis smoke inhalation, in male ICR mice (Lichtman et al, 2000;Lichtman, Poklis, Poklis, Wilson & Martin, 2001). Catalepsy caused by marijuana smoke inhlation was not blocked by SR pretreatment in the latter study.…”
Section: Introductionmentioning
confidence: 55%
“…However, contradictory findings have also been published, with either no change 54 or even a decrease 55 in anxiety-like behavior after cannabinoid exposure in adolescence. Rats that were exposed to cannabis smoke were also reported to exhibit a decrease in anxiety-like behavior 56 . Interestingly, a previous study also demonstrated that long-term cognitive and behavioral dysfunction that was induced by adolescent THC exposure could be prevented by concurrent cannabidiol treatment 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Our prior work found female adult rats became tolerant after a repeated THC vapor inhalation regimen that did not produce tolerance in male adults (Nguyen, J. D. et al, 2018a). Adult male rats (females were not assessed) exposed to repeated marijuana smoke did not exhibit cross-tolerance to the locomotor suppressing effects of the endogenous cannabinoid agonist anandamide (Bruijnzeel et al, 2016). The finding of significantly lower bodyweight in the males during the second treatment week (Figure S3) is similar to evidence that repeated THC injections during adolescence reduced weight gain in male and female Wistar and Long-Evans rats in a 14 day treatment interval (Keeley et al, 2015) and in male Wistar rats during an 8 day repeated-injection study (Sofia and Barry, 1974).…”
Section: Discussionmentioning
confidence: 99%